Image Tracking Berbasis AR Untuk Peningkatan Pembelajaran Buah Pada Pendidikan Anak Usia Dini (PAUD) - Agustinus Rudatyo Himamunanto; Desri A.F. Waruwu; Gogor C. Setyawan (Fakultas Teknik Universitas Hamzanwadi, 2023)
The current recognition and learning system still uses magazines, books and websites. This makes the lessons of the topics taught still difficult to understand. In this study, a fruit recognition learning model was created in early childhood education based on Augmented Reality and digitalized teaching aids. Augmented Reality is a technology that embodies the merging of the real world (reality) and virtual world (virtual) where this technology is also known as Virtual Reality. The marker in the form of an image will be captured by the camera, processed and a 3D fruit animation will appear on the mobile screen. The purpose of this research is to produce a fruit recognition learning model in PAUD TK Aba Sukoharjo Kalasan based on Augmented Reality and to create digitalized teaching aids. By using Augmented Reality the application can be educational and attract interest in children's curiosity. The method used in this study is the Multimedia Development Life Cycle (MDLC). The fruit recognition application has been applied to several child respondents. Based on research trials, before there was an application for interest in learning, children learned fruit recognition with a score of 73% with the predicate agreeing. The effect of positive trends on children to learn with augmented reality learning media is shown by a score of 81% of 30 child respondents stating that the application is very effective as an increase in the recognition of fruits